Complications of Heart Valve Replacement—Embolism, Bleeding and Hemolysis - Mc Henry, Malcolm M. (1968)
Fifty-two patients surviving single heart valve replacement since September 1962 were reviewed in order to detail the incidence of post-operative embolism, bleeding and hemolysis. A substantial decrease in the occurrence of embolism has been seen with newer prosthetic devices paralleling the improvement in cardiac catheterization dynamics. The frequency of embolism appears also to be affected by the degree and adequacy of anticoagulant control although a higher morbidity from bleeding must be accepted. The tendency to deformation and destruction of red cells by rigid prosthetic valves is apparent since shortened red cell survival indicative of hemolysis was found in all patients studied. Hemolytic anemia of importance was uncommon.